Retrieval of Volcanic Sulphate Aerosols Optical Parameters from AHI Radiometer Data - Filei Andrei; Girina O.A.; Sorokin A.A. (Chinese Academy of Sciences, 2024)
This paper presents a method for retrieving volcanic sulphate aerosols optical parameters from the AHI radiometer on board the Himawari-8 satellite. The proposed method is based on optical models for various mixtures of the volcanic cloud’s aerosol components, including ash particles, ice crystals, water drops, and sulphate aerosol droplets. The application of multicomponent optical models of various aerosol compositions allowed the optical thickness and mass loading of sulphate aerosol to be estimated in the sulfuric cloud formed after the Karymsky volcano eruption on November 3, 2021. A comprehensive analysis of the brightness temperatures of the sulfuric cloud in the infrared bands was performed, which revealed that the cloud composed a mixture of sulphate aerosol and water droplets. The use of the models of various aerosol composition allows the satellite-based estimation of optical parameters not only for sulphate aerosol but also for the whole aerosol mixture.
Keywords: 37.21.15 Строение и состав атмосферы; 37.21.37 Атмосферная циркуляция; Карымский